2017
DOI: 10.1186/s12862-017-1027-7
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA structure: the women who formed the Brazilian Northeast

Abstract: BackgroundThe distribution of mitochondrial DNA (mtDNA) lineages in Brazil is heterogeneous due to different regional colonization dynamics. Northeastern Brazil, although being an important region in terms of human imigration and ethnic admixture, has little information regarding its population mtDNA composition. Here, we determine which mitochondrial lineages contributed to the formation of the Northeastern Brazilian population. Our sample consisted of 767 individuals distributed as follows i) 550 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
6
15
1
2
Order By: Relevance
“…Such small contributions of African and, ever more so, of Native American haplogroups are in accordance with Ychromosome data from other European colonies in South America, despite them being the majority in mtDNA studies (46)(47)(48)(49). In fact, previous mtDNA data obtained by Schaan et al (13) for the same samples demonstrated a strong Amerindian (43.5%) and African (37.8%) female component in Northeast Brazil. These findings attest to the strong asymmetric colonization favoring the introgression of European Y lineages in this region, a pattern that has been reported for other Brazilian regions and is typical for South American countries as well (50).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Such small contributions of African and, ever more so, of Native American haplogroups are in accordance with Ychromosome data from other European colonies in South America, despite them being the majority in mtDNA studies (46)(47)(48)(49). In fact, previous mtDNA data obtained by Schaan et al (13) for the same samples demonstrated a strong Amerindian (43.5%) and African (37.8%) female component in Northeast Brazil. These findings attest to the strong asymmetric colonization favoring the introgression of European Y lineages in this region, a pattern that has been reported for other Brazilian regions and is typical for South American countries as well (50).…”
Section: Discussionsupporting
confidence: 89%
“…These samples are a subset of those previously investigated for mtDNA data. See Schaan et al (13) for biological material acquirement and DNA extraction methodology.…”
Section: Population Sample and Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, análises das regiões hipervariáveis do mtDNA revelaram uma realidade diferente: considerando o Brasil como um todo, 39% da ancestralidade materna é de origem europeia, 33% de origem ameríndia e 28% africana (Alves-Silva et al, 2000;Fridman et al, 2014;Schaan et al, 2017). Significativamente, a frequência de ancestralidade do mtDNA variou muito nas diferentes regiões: a maior porcentagem de ancestralidade materna ameríndia (54%) esteve presente na região Norte, enquanto que a ancestralidade africana é maior no Nordeste (44%) e a ancestralidade europeia é predominante no Sul (66%) (Alves-Silva et al, 2000).…”
Section: Lista Gráficounclassified
“…Juntos, esses dados revelam que a contribuição genética europeia foi basicamente por meio dos homens, enquanto que a contribuição genética africana e ameríndia aconteceu, principalmente, pelas mulheres (Alves-Silva et al, 2000;Carvalho-Silva et al, 2001;Carvalho-Silva et al, 2006;Fridman et al, 2014;Pena et al, 2011;Resque et al, 2016;Schaan et al, 2017;Simão et al, 2018).…”
Section: Lista Gráficounclassified